Efforts to Improve Learning Outcomes Using Lumatika Media in Mathematics Subjects in Grade III at Elementary Schools In East Jakarta - Muhammad Ihwan Rois; Septi Fitri Meilana (Eduvest - Journal of Universal Studies, 2024)
Learning is an effort made by teachers to educate students to develop their understanding of certain knowledge. The use of media in learning is very important to improve student learning outcomes. The right media can convey information clearly and stimulate learning activities. Lumatika media, which is interactive and innovative, is designed to improve understanding of mathematical concepts through the use of real and interesting props. This research was conducted in the 3rd grade of SDN Wilayah Jakarta Timur to overcome the low learning outcomes of students in mathematics. The method used was classroom action research with four stages: planning, implementation, observation, and reflection. Data collection was done through observation, interviews, tests, and documentation. The results showed that the use of Lumatika media improved students' math learning outcomes. In cycle I, the percentage of learning completeness reached 53%, increased to 88% in cycle II, and reached 94% in cycle III. The conclusion is that the use of Lumatika media is effective in improving the math learning outcomes of grade 3 students at SDN East Jakarta.